Global water distribution in the mantle transition zone from a seismic isotropic velocity model and mineral physics modeling - Wang, Zongfa; Wang, Yi (Frontiers in Earth Science, 2022)
Although the discovery of hydrous ringwoodite inclusions and ice-VII inclusions in natural diamonds suggest a hydrous mantle transition zone (MTZ), water content and distribution in the MTZ remain unclear. Here combining a global P- and S-wave isotropic velocity tomography and mineral physics modeling, we image the water distribution in the MTZ. Our results indicate that the MTZ is a main water reservoir inside the Earth, and the total water content of the MTZ is about 2/3 seawater. The upper MTZ (410 km - 520 km) and the lower MTZ (520 km - 660 km) contain 0.3 wt.% and 0.15 wt.% water, respectively, implying water contents of the MTZ decrease with increasing depths. The most hydrous regions are mainly located near subduction zones, where the upper MTZ and the lower MTZ can contain water up to 0.5 - 1 wt.% and 0.2 - 0.5 wt.%, respectively, indicating water is transported into the MTZ by hydrous slabs. In addition, old subducted slabs in the western Pacific subduction zone are more hydrous than young subducted slabs in the eastern Pacific subduction zone. We also propose a water circulation model which integrates our results of the water content and distribution in the MTZ.